2018
DOI: 10.1039/c8ta04074e
|View full text |Cite
|
Sign up to set email alerts
|

Biowaste crab shell-extracted chitin nanofiber-based superior piezoelectric nanogenerator

Abstract: A simple, cost-effective and environment-friendly biowaste crab shell-extracted chitin nanofiber-based superior piezoelectric nanogenerator was fabricated in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(97 citation statements)
references
References 54 publications
2
84
2
1
Order By: Relevance
“…In spite of that, biocompatibility and bioavailability are major issues that determines the potential areas of application which is the main reason for the replacement of hazardous nanoparticles with biocompatible ones [17]. In recent times, some studies show that the researchers are focussing on biocompatible nano-systems to fabricate efficient and cost-effective organic solar cells [18], heavy metal sensors [19][20][21], gas sensors [22] and energy harvesting devices such as nanogenerators [23] and supercapacitors [24][25][26]. These next-generation nano-systems and nano-devices are capable to reduce environmental pollution and delivers greater efficiency [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…In spite of that, biocompatibility and bioavailability are major issues that determines the potential areas of application which is the main reason for the replacement of hazardous nanoparticles with biocompatible ones [17]. In recent times, some studies show that the researchers are focussing on biocompatible nano-systems to fabricate efficient and cost-effective organic solar cells [18], heavy metal sensors [19][20][21], gas sensors [22] and energy harvesting devices such as nanogenerators [23] and supercapacitors [24][25][26]. These next-generation nano-systems and nano-devices are capable to reduce environmental pollution and delivers greater efficiency [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…a Glycine intermolecular dipoles when the amino acid is crystallized in a monoclinic space group. b Open circuit voltages generated by biological energy harvesters in the past decade 10,26,[39][40][41][42][43][44] . c Comparison of the piezoelectric strain constants of a variety of biomaterials versus their inorganic counterparts.…”
mentioning
confidence: 99%
“…g) Dependence of piezoelectric strain constant d 14 = d′ 14 − id″ 14 with temperature for dried α-chitin measured at 10 Hz. Ray and co-workers [113] studied piezoelectric effect on chitin nanofibers, extracted from crab shell and achieved piezoelectric constant (d 33 ) of ≈9.49 pC N −1 . [110] Copyright 1975, WILEY-VCH.…”
Section: Polysaccharides Based Materialsmentioning
confidence: 99%
“…PSChNFs is an excellent piezoelectric material and biocompatible can be used for green energy source and health care maintaining system. Ray and co‐workers studied piezoelectric effect on chitin nanofibers, extracted from crab shell and achieved piezoelectric constant ( d 33 ) of ≈9.49 pC N −1 . Recently, Schauer et al observed the variable piezoelectric effect of electrospun chitin nanofibers.…”
Section: Piezoelectricity Of Nature Driven Bio‐piezoelectric Materialsmentioning
confidence: 99%